Fiscal Consolidation and the New Flat Rate Individual Income Tax in Hungary - Mihály Hıgye (European Financial and Accounting Journal, 2011)
In the last two years the Hungarian people have witnessed several new measures in government's fiscal policy. To respond to global crisis that hit Hungary hard, the Bajnai government enacted a series of economic reforms and spending cuts in 2009. The Orban government elected in 2010 launched economic programs designed to promote growth by reducing administrative burdens on businesses and lowering the tax burdens on small businesses. The plan also includes strict control of budgetary expenditures, and a “crises-tax” on different sectors which would remain in effect for minimum 2 years. One of the most popular plans seems to be the launch of a “flat-rate” individual tax replacing the existing progressive tax aiming to increase supply of labor and so tax base, to improve tax compliance and the reduce cost of taxation. The paper analyses the recent changes from theoretical and practical views focusing on expected effects of the new flat rate individual income tax system. At first glance it seems to be that this new fiscal measure has just basically anti-consolidation effects on government budgetary position loosing significant revenues from income taxes. From international lessons it is expected that that there will be no Laffer-type behavioral responses generating revenue increases from the tax cut elements of the reform. The impact of the flat tax on work incentives might be expected only in short run. The flat rate reduces the flexibility of government to use tax rates as one of the “strong” weapons in budgetary policy when it becomes unavoidable. In many developed countries a wide range of tax expenditure is still applied in a more or less progressive personal income tax system. In a system where tax expenditures are widely used tax compliance may systematically improved if burdens and benefits are linked.
Keywords: H2; 650; Fiscal policy; Tax principles; Tax system; Flat rate tax; Social policy